Conjugated polymer as well as preparation method and application thereof

By designing conjugated polymers connected to EDOT units with trifluoromethylbenzene or trifluoromethoxybenzene, and preparing by electrochemical polymerization methods, the problems of poor stability and low optical contrast of existing conductive polymer electrochromic materials are solved. Achieve efficient and stable electrochromic performance.

CN119463130APending Publication Date: 2025-02-18WUYI UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411428312.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-14
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

Existing conductive polymer electrochromic materials have problems such as poor stability and low optical contrast, which is difficult to meet the needs of efficient electrochromic performance.

Method used

Design a conjugated polymer, which uses trifluoromethylbenzene or trifluoromethoxybenzene as conjugated acceptor units, and connects strong electron donation EDOT units on both sides, and prepares them by electrochemical polymerization to form excellent electrogenesis Materials with color distortion properties.

Benefits of technology

It has achieved wider redox peaks, better redox activity, good optical contrast, fast response time, and high characteristics, which significantly improves the stability and electrochromic properties of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005082828160000021
    Figure BDA0005082828160000021
  • Figure BDA0005082828160000022
    Figure BDA0005082828160000022
  • Figure BDA0005082828160000031
    Figure BDA0005082828160000031
Patent Text Reader

Abstract

The invention discloses a hybrid conjugated polymer with trifluoromethyl benzene or trifluoromethoxybenzene as a core unit and EDOT units connected to two sides as well as a preparation method and application of the hybrid conjugated polymer, and belongs to the field of polymer electrochromic materials. According to the invention, the strong electron-donating group EDOT is connected to the sites 2 and 5 or the sites 3 and 5 of trifluoromethyl benzene or trifluoromethoxybenzene, so that the obtained hybrid conjugated polymer has the characteristics of wider redox peak, good optical contrast, fast response time, high coloring efficiency, good stability and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of polymer electrochromic materials, and in particular relates to a conjugated polymer and a preparation method and application thereof. Background Art

[0002] Electrochromic materials can achieve reversible changes in optical properties (color, reflectivity, transmittance) under the action of an external electric field. Organic electrochromic materials can achieve rich spectral regulation due to the designable properties of their molecular structure, and thus show good application prospects in the field of dynamic spectral regulation. Among them, polymer electrochromic materials have attracted attention due to their low cost, versatility, flexibility and excellent performance. The key to the design of new and efficient organic polymers lies in regulating their optoelectronic properties and molecular stacking properties.

[0003] Although great progress has been made in the structural design of polymers, conductive polymer electrochromic materials also have their own limitations, such as poor stability of some polymers and low optical contrast. Therefore, it is necessary to develop polymer electrochromic materials with good stability and excellent electrochromic properties. Summary of the invention

[0004] The present invention aims to solve at least one of the technical problems existing in the above-mentioned prior art. To this end, the present invention provides a conjugated polymer. The conjugated polymer uses trifluoromethylbenzene or trifluoromethoxybenzene as a conjugated acceptor unit, and strong electron-donating EDOT units are connected on both sides, so that the obtained conjugated polymer has a wider redox peak and better redox activity, and has good optical contrast, fast response time, high coloring efficiency, good stability and the like when used in electrochromic materials.

[0005] The invention also provides a method for preparing the conjugated polymer.

[0006] The invention also provides an electrochromic material.

[0007] The invention also provides an application of the conjugated polymer in an electrochromic device.

[0008] According to one aspect of the present invention, a conjugated polymer is provided, the structural formula of which is shown in formula (I) or formula (II):

[0009]

[0010] In formula (1) and formula (2), n is independently 3 to 100.

[0011] In the present invention, the trifluoromethyl or trifluoromethoxy substitution on the phenyl unit not only deepens the HOMO energy level of the monomer and its polymer, but also increases the optical band gap. The trifluoromethyl and trifluoromethoxy substitution of the present invention has several advantages in regulating the π electron behavior of organic semiconductors: (1) the flexible fluorinated group helps to improve the solubility and electrochemical stability of the polymer due to its unique physicochemical properties (strong inductive effect and hyperconjugation effect); (2) it has a strong electron-withdrawing effect, and the polymer has a more obvious spectral absorption change under different voltages; (3) the fluorinated group is easy to obtain, and the synthesis is simple and low-cost.

[0012] The conjugated polymer of trifluoromethylbenzene or trifluoromethoxybenzene connected to EDOT units provided by the present invention has a 3 The high electronegativity value (up to 3.5) and the F atom enhance the intermolecular CF…H, F…S, CF…π interactions, which have various positive effects on the photoelectric properties, energy levels, planarity and crystallinity of the polymer. Therefore, the conjugated polymer of the present invention has good electrochemical stability, optical contrast and short response time.

[0013] The conjugated polymer of the present invention has the characteristics of low bandwidth, rich colors, fast response time, high coloring efficiency, etc. when used in electrochromic materials by connecting a strong electron-donating group EDOT at the 2nd and 5th sites or the 3rd and 5th sites of trifluoromethylbenzene or trifluoromethoxybenzene.

[0014] According to another aspect of the present invention, a method for preparing the above conjugated polymer is provided, wherein the conjugated polymer is prepared from an active precursor by an electrochemical polymerization method; the structural formula of the active precursor is shown in formula (1) or formula (2):

[0015]

[0016] The preparation method of the invention is simple, the raw materials are readily available, the production cost is low, and it is easy to industrialize and mass produce.

[0017] In some embodiments of the present invention, the method for preparing the active precursor comprises: under the protection of an inert gas, subjecting an acceptor compound to a stannic compound of EDOT in a catalyst and a solvent for a Stille or Suzuki cross-coupling reaction, thereby obtaining the active precursor;

[0018] The receptor compound is 2,5-dibromotrifluoromethylbenzene or 3,5-dibromotrifluoromethylbenzene.

[0019] In some embodiments of the present invention, the inert gas comprises argon or nitrogen.

[0020] In some embodiments of the present invention, the tin hydrocarbon compound of EDOT is 5-tributyltin-3,4-vinyldioxythiophene, ie, tributyl(2,3-dihydro[3,4-b][1,4]dioxin-5-yl)stannane.

[0021] In some embodiments of the present invention, the catalyst comprises tetrakistriphenylphosphine palladium (Pd(PPh 3 ) 4 ) or bis(triphenylphosphine palladium dichloride (Pd(PPh 3 ) 2 Cl 2 ) at least one of.

[0022] In some embodiments of the present invention, the solvent includes at least one of toluene and N,N-dimethylformamide (DMF).

[0023] In some embodiments of the present invention, the molar ratio of the acceptor compound, the tin hydrocarbon compound of EDOT and the catalyst is 1:2-3:0.03-0.1; in some embodiments of the present invention, the molar ratio of the acceptor compound, the tin hydrocarbon compound of EDOT and the catalyst is 1:2-3:0.04-0.07; for example, 1:2.5:0.05.

[0024] In some embodiments of the present invention, the temperature of the Stille or Suzuki cross-coupling reaction is 100°C to 120°C; for example, it can be about 100°C, about 105°C, about 110°C or about 120°C.

[0025] In some embodiments of the present invention, the reaction time of the Stille or Suzuki cross-coupling reaction is 24 h to 48 h; for example, it can be about 24 h, about 28 h, about 32 h, about 36 h, about 40 h or about 48 h.

[0026] According to some specific embodiments of the present invention, the active precursor is prepared by any one of the following reaction equations:

[0027]

[0028] In some embodiments of the present invention, the method for preparing the active precursor further includes the step of purifying the product obtained by the reaction, including but not limited to rotary evaporation, reduced pressure distillation and column chromatography (eg, silica gel column chromatography).

[0029] In some embodiments of the present invention, the electrochemical polymerization method comprises using a solution containing the active precursor as an electrolyte solution, and performing electrodeposition in a three-electrode system consisting of a reference electrode, a counter electrode and a working electrode to obtain a thin film material of the conjugated polymer.

[0030] In some embodiments of the present invention, the working electrode comprises a glassy carbon electrode or ITO conductive glass, the counter electrode comprises a platinum electrode (eg, a platinum wire), and the reference electrode comprises an Ag / AgCl electrode.

[0031] In some embodiments of the present invention, the electrochemical polymerization method is carried out in a protective gas.

[0032] In some embodiments of the present invention, the protective gas comprises argon or nitrogen.

[0033] In some embodiments of the present invention, the electrolyte solution further includes a solvent.

[0034] In some embodiments of the present invention, the solvent comprises dichloromethane (CH 2 Cl 2 ), chloroform (CHCl 3 ) or at least one of acetonitrile (MeCN).

[0035] In some embodiments of the present invention, the electrolyte solution further contains a supporting electrolyte.

[0036] In some embodiments of the present invention, the supporting electrolyte comprises tetrabutylammonium hexafluorophosphate (Bu 4 NPF 6 ), Tetrabutylammonium tetrafluoroborate (Bu 4 NBF 4 ) or lithium perchlorate (LiClO 4 ) at least one of.

[0037] In some embodiments of the present invention, the concentration of the active precursor in the electrolyte solution is 0.001 to 0.01 mol·L -1 ; For example, about 0.001 mol·L -1 , about 0.002 mol·L -1 , about 0.005 mol·L -1 , about 0.008 mol·L -1 or about 0.01 mol·L -1 .

[0038] In some embodiments of the present invention, the concentration of the supporting electrolyte is 0.05 to 0.15 mol·L -1 Preferably, the concentration of the supporting electrolyte is 0.075 to 0.125 mol·L -1 In a more preferred embodiment, the concentration of the supporting electrolyte is about 0.1 mol·L -1 .

[0039] In some specific embodiments of the present invention, the conjugated polymer of the benzene derivative linked to EDOT is prepared by one of the following reaction equations:

[0040]

[0041] In some embodiments of the present invention, the electrochemical polymerization method uses constant potential method, constant current method or cyclic voltammetry method for electrodeposition.

[0042] In some embodiments of the present invention, the electrochemical polymerization method uses a constant potential method for electrodeposition.

[0043] In some preferred embodiments of the present invention, the potential of the electrodeposition is 0.8V to 1.2V; for example, it may be about 0.8V, about 0.9V, about 1.0V, about 1.1V or about 1.2V; preferably 0.8 to 1.0V.

[0044] In some preferred embodiments of the present invention, the electrodeposition time is 80s to 200s; for example, the electrodeposition time is about 80s, about 100s, about 120s, about 140s, about 160s, about 180s or about 200s; preferably 100-160s.

[0045] In some preferred embodiments of the present invention, the electrodeposition potential is about 0.9 V and the time is about 120 s.

[0046] According to yet another aspect of the present invention, an electrochromic material is provided, which comprises the above-mentioned conjugated polymer or the conjugated polymer prepared by the above-mentioned preparation method.

[0047] According to another aspect of the present invention, the use of the above conjugated polymer or the conjugated polymer prepared by the above preparation method in an electrochromic device is proposed. The electrochromic device includes but is not limited to at least one of electrochromic glass, display, smart window or rearview mirror. Since there are certain requirements for the waterproofness of the device in current industrial applications, the conjugated polymer material of the present invention has a -CF 3 The introduction of is beneficial to preventing water penetration in the device, thereby improving the stability of the corresponding device.

[0048] The beneficial technical effects of the present invention are:

[0049] 1. The hybrid conjugated polymer of the present invention has trifluoromethylbenzene or trifluoromethoxy as the core unit and EDOT units connected on both sides, and has a conjugated structure, and the energy band gap of the polymer can be adjusted by the π-π* conjugation strength, thereby changing the color of the polymer.

[0050] 2. The conjugated polymer of the present invention has good planarity based on benzene, and the trifluoromethyl and trifluoromethoxy groups have strong electronegativity, so that the receptor unit has similar functional effects to traditional DA type receptors. At the same time, trifluoromethylbenzene and trifluoromethoxybenzene have high economic efficiency, which makes them have greater potential in practical applications.

[0051] 3. The hybrid conjugated polymer of the benzene derivative of the present invention combined with the strong electron donating group of 3,4-ethylenedioxythiophene (EDOT) has a shorter response time, good coloring efficiency and stability, better optical contrast and distinct color change as characterized by electrochromic performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0052] The present invention will be further described below with reference to the accompanying drawings and embodiments, wherein:

[0053] Figure 1 P(TFB-2,5-EDOT) of Example 1 in MeCN-Bu 4 NPF 6 (0.1mol·L -1 ) system.

[0054] Figure 2 The transmittance-time curves of P(TFB-2,5-EDOT) of Example 1 at 600 nm, 800 nm and 1100 nm.

[0055] Figure 3 To implement 2, P(TFOB-2,5-EDOT) in MeCN-Bu 4 NPF 6 (0.1mol·L -1 ) system.

[0056] Figure 4 The transmittance-time curves of P(TFOB-2,5-EDOT) of Example 2 at 486 nm, 690 nm and 1100 nm. DETAILED DESCRIPTION

[0057] The following will be combined with the embodiments to clearly and completely describe the concept of the present invention and the technical effects produced, so as to fully understand the purpose, characteristics and effects of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, other embodiments obtained by those skilled in the art without creative work are all within the scope of protection of the present invention.

[0058] Unless otherwise indicated herein, recitation of ranges of values ​​herein is merely intended to serve as a shorthand method of referring individually to each separate value falling within the range, and each separate value is incorporated into the specification as if it were individually recited herein. Unless otherwise indicated herein, all exact values ​​provided herein represent corresponding approximate values ​​(e.g., all exact exemplary values ​​provided with respect to a particular factor or measurement can be considered to also provide corresponding approximate measurements, modified by "about" where appropriate).

[0059] As used herein, when used in connection with a numerical value, the term "about" is intended to include a set or range of numerical values. For example, "about" means a numerical range of ±5%, ±2%, ±1%, ±0.5%, ±0.2% or ±0.1% of the numerical value. In one embodiment, the term "about" refers to a numerical range of 5% more or less than a specific value. In another embodiment, the term "about" refers to a numerical range of 2% more or less than a specific value. In another embodiment, the term "about" refers to a numerical range of 1% more or less than a specific value.

[0060] The test methods used in the examples are conventional methods unless otherwise specified; the materials, reagents, etc. used, unless otherwise specified, can be obtained from commercial sources. Unless otherwise specified, the same parameter values ​​in each example are the same. The examples described below are exemplary and are only used to explain the present invention, and should not be construed as limiting the present invention.

[0061] In the present invention, the coloring efficiency refers to the ratio of the change in absorbance of the electrochromic material at a given wavelength to the total electron injection or extraction.

[0062] For an electrochromic material, coloring efficiency is an important parameter for evaluating material performance. The coloring efficiency of conductive polymers should be studied in combination with the electrochemical and spectral changes of the electrochromic film. The calculation formula is as follows:

[0063] ΔOD=log(T ox / T red ) (1)

[0064] Q d =(Q ox +Q red ) / S (2)

[0065] CE=ΔOD / Q d (3)

[0066] Where ΔOD is the logarithmic value of the ratio of the transmittance of the material under different states at a specified wavelength; Q d is the amount of charge flowing through the material per unit area (C / cm 2);CE is the coloring efficiency of the material (cm 2 / C); T ox is the transmittance of the electrochromic material in the oxidized state (%); T red is the transmittance of the electrochromic material in the reduced state (%); Q ox is the charge during the oxidation process (C); Q red is the charge during the reduction process (C); S is the area of ​​the working electrode (cm 2 ).

[0067] Example 1

[0068] (1) Synthesis of TFB-2,5-EDOT active precursor

[0069]

[0070] Under nitrogen atmosphere, 2,5-dibromotrifluoromethylbenzene (1.64 mmol, 0.5 g), tributyl(2,3-dihydro[3,4-b][1,4]dioxin-5-yl)stannane (4.1 mmol, 1.772 g), and catalyst Pd(PPh 3 ) 4 (0.076mmol, 0.088g) was placed in a 250mL single-necked flask, and dry toluene (Tol) (80mL) and N,N-dimethylformamide (DMF) (20ml) were added and stirred evenly, and heated to 120°C for condensation and reflux reaction for 48 hours. After the system was cooled, toluene was removed by rotary evaporator; dichloromethane was added for extraction, and the organic layer was washed with pure water to remove DMF in the organic layer, and then the solvent was removed by reduced pressure distillation and rotary evaporation, and separated by silica gel chromatography column, and the eluent was DCM:PE=1:3, and the white powder product TFB-2,5-EDOT was purified.

[0071] (2) Electrochemical synthesis of P(TFB-2,5-EDOT) conjugated polymer

[0072]

[0073] Under the protection of argon, electrochemical polymerization was carried out in a three-electrode system, with a silver / silver chloride electrode as a reference electrode, a platinum wire as a counter electrode, and an ITO glass as a working electrode; 10 mL of dichloromethane was used as the solvent, Y2Cl-EDOT (0.0043 g, 0.01 mmol) was used as the polymerization monomer, and tetrabutylammonium hexafluorophosphate (0.3874 g, 1 mmol) was used as the supporting electrolyte; the polymerization was carried out using a constant potential method, with a polymerization potential of 0.93 V and a polymerization time of 120 s. The polymer film obtained by electrodeposition was soaked and rinsed with acetonitrile to remove the electrolyte and precursor in the polymer. Afterwards, the obtained polymer film was placed in MeCN-Bu 4 NPF 6 (0.1mol·L -1 ) system for spectroelectrochemical characterization.

[0074] (3) Study on electrochromic properties (i) Combination Figure 1 , observe the color change of the polymer material with the naked eye. It can be seen that with the increase of potential, the color of the polymer material changes from blue to gray. This is because the neutral polymer material has an absorption peak in the visible light region and the red light region, and the color of the neutral polymer material is blue; after the polymer material is oxidized, the absorption peak in the visible light region gradually weakens, the absorption peak in the red light region gradually increases, and finally the absorption peak in the visible light region completely disappears; therefore, the polymer material in the completely dedoped state appears blue, and the doped polymer material appears gray.

[0075] (ii) The response time and coloring efficiency calculated from the time-transmittance curve are shown in Table 1.

[0076] Table 1 Electrochromic parameters of P(TFB-2,5-EDOT)

[0077]

[0078]

[0079] In this embodiment, the optical transmittance of P(TFB-2,5-EDOT) was studied by the timed absorption method at wavelengths of 600nm, 800nm ​​and 1100nm. During the experiment, the sawtooth wave period of potential and time was 5s. Figure 2 As shown. Under the three wavelengths, the polymer material exhibits a certain optical contrast and good optical stability; in addition, the optical transmittance has a great influence on the color change of the polymer material, and the polymer material can be transformed from blue in a completely dedoped state to gray in a doped state.

[0080] Example 2

[0081] (1) Synthesis of TFOB-2,5-EDOT active precursor

[0082]

[0083] Under nitrogen atmosphere, 2,5-dibromotrifluoromethoxybenzene (1.56 mmol, 0.5 g), tributyl(2,3-dihydro[3,4-b][1,4]dioxin-5-yl)stannane (3.9 mmol, 1.688 g), and catalyst Pd(PPh 3 ) 4 (0.063mmol, 0.072g) was placed in a 250mL single-necked flask, and dry toluene (80mL) and N,N-dimethylformamide (DMF) (20ml) were added and stirred evenly, and heated to 120°C for condensation and reflux reaction for 48 hours. After the system was cooled, toluene was spun out by a rotary evaporator; dichloromethane was added for extraction, and the organic layer was washed with pure water to remove DMF in the organic layer, and then the solvent was removed by reduced pressure distillation and rotary evaporation, and separated by a silica gel chromatography column, and the eluent was DCM:PE=1:3, and the white powder product TFOB-2,5-EDOT was purified.

[0084] (2) Electrochemical synthesis of P(TFOB-2,5-EDOT) conjugated polymer

[0085]

[0086] Under the protection of argon, electrochemical polymerization was carried out in a three-electrode system, with a silver / silver chloride electrode as a reference electrode, a platinum wire as a counter electrode, and a glassy carbon as a working electrode; 10 mL of dichloromethane was used as the electrolyte, TFOB-2,5-EDOT (0.0044 g, 0.01 mmol) was used as the polymerization monomer, and tetrabutylammonium hexafluorophosphate (0.3874 g, 1 mmol) was used as the supporting electrolyte; the polymerization was carried out by constant potential method, the polymerization potential was 0.9 V, and the polymerization time was 120 s. The polymer film obtained by electrodeposition was soaked and rinsed with acetonitrile to remove the electrolyte and precursor in the polymer. The obtained polymer film was placed in MeCN-Bu 4 NPF 6 (0.1mol·L -1 ) system for spectroelectrochemical characterization.

[0087] (3) Study on electrochromic properties (i) Combination Figure 3, observe the color change of the polymer material with the naked eye. It can be seen that with the increase of potential, the color of the polymer material changes from light red to dark purple. This is because the neutral polymer material has an absorption peak in the purple light region and the red light region, and the color of the neutral polymer material is light red; after the polymer material is oxidized, the absorption peak in the purple light region gradually weakens and finally disappears completely, and the absorption peak in the red light region gradually increases; therefore, the polymer material in the completely dedoped state appears light red, and the doped polymer material appears dark purple.

[0088] (ii) The response time and coloring efficiency calculated from the time-transmittance curve are shown in Table 2.

[0089] Table 2 Electrochromic parameters of P (TFOB-2,5-EDOT)

[0090]

[0091] The optical transmittance of P(TFOB-2,5-EDOT) was studied by timed absorption method at wavelengths of 486nm, 690nm and 1100nm. During the experiment, the time interval of the potential step change was 5s. Figure 4 As shown. Under the three wavelengths, the polymer material exhibits a certain optical contrast and good optical stability; in addition, the optical transmittance has a great influence on the color change of the polymer material, and the polymer material can be transformed from light red in the completely dedoped state to dark purple in the doped state.

[0092] Comparative Example 1

[0093] (1) Synthesis of TFB-3,5-EDOT active precursor

[0094]

[0095] Under nitrogen atmosphere, 3,5-dibromotrifluoromethylbenzene (1.64 mmol, 0.5 g), tributyl(2,3-dihydro[3,4-b][1,4]dioxin-5-yl)stannane (4.1 mmol, 1.772 g), and catalyst Pd(PPh 3 ) 4(0.076mmol, 0.088g) was placed in a 250mL single-necked flask, and dry toluene (Tol) (80mL) and N,N-dimethylformamide (DMF) (20ml) were added and stirred evenly, and heated to 120°C for condensation and reflux reaction for 48 hours. After the system was cooled, toluene was removed by rotary evaporator; dichloromethane was added for extraction, and the organic layer was washed with pure water to remove DMF in the organic layer, and then the solvent was removed by reduced pressure distillation and rotary evaporation, and separated by silica gel chromatography column, and the eluent was DCM:PE=1:3, and the white powder product TFB-3,5-EDOT was purified.

[0096] (2) During the electrochemical synthesis process, no film was found to be formed on the glassy carbon electrode, and from the deposition cyclic voltammetry (CV) diagram, the current density showed a decreasing trend with the increase in the number of scans, indicating that TFB-3,5-EDOT could not be electrochemically polymerized to obtain the corresponding polymer and polymer film.

[0097] Comparative Example 2

[0098] (1) Synthesis of TFOB-3,5-EDOT active precursor

[0099]

[0100] Under nitrogen atmosphere, 3,5-dibromotrifluoromethoxybenzene (1.56 mmol, 0.5 g), tributyl(2,3-dihydro[3,4-b][1,4]dioxin-5-yl)stannane (3.9 mmol, 1.688 g), and catalyst Pd(PPh 3 ) 4 (0.063mmol, 0.072g) was placed in a 250mL single-necked flask, and dry toluene (80mL) and N,N-dimethylformamide (DMF) (20ml) were added and stirred evenly, and heated to 120°C for condensation and reflux reaction for 48 hours. After the system was cooled, toluene was removed by rotary evaporator; dichloromethane was added for extraction, and the organic layer was washed with pure water to remove DMF in the organic layer, and then the solvent was removed by reduced pressure distillation and rotary evaporation, and separated by silica gel chromatography column, the eluent was DCM:PE=1:3, and the white powder product TFOB-3,5-EDOT was purified.

[0101] (2) During the electrochemical synthesis process, no film was found to be formed on the glassy carbon electrode, and from the deposition cyclic voltammetry (CV) diagram, the current density showed a decreasing trend with the increase in the number of scans, indicating that TFOB-3,5-EDOT could not be electrochemically polymerized to obtain the corresponding polymer and polymer film.

[0102] It can be seen from Examples 1-2 and Tables 1-2 that, under the action of an applied voltage, a stable and reversible color change to blue or gray can be observed in Example 1, and a stable and reversible color change to light red or dark purple can be observed in Example 2; the prepared conjugated polymer has a fast response time and a high coloring efficiency when used for electrochromism.

[0103] The absorption position of the polymer determines the color of the polymer, which is of great significance for the preparation of electrochromic polymers of various colors. The response time is also an important parameter of electrochromic materials, which reveals the speed at which the doped ions enter the polymer main chain during the doping process. The conjugated polymer of trifluoromethylbenzene or trifluoromethoxybenzene connected to the EDOT unit provided by the present invention has a -CF 3 The high electronegativity value and the F atom enhance the intermolecular CF…H, F…S, CF…π interactions, which have various positive effects on the photoelectric properties, energy levels, planarity and crystallinity of the polymer. Therefore, the conjugated polymer of the present invention has good electrochemical stability, optical contrast and short response time.

[0104] In summary, the conjugated polymer of the present invention connects a strong electron donating group EDOT to the 2nd and 5th sites or the 3rd and 5th sites of trifluoromethylbenzene or trifluoromethoxybenzene, and a stable and reversible color change from blue to gray or light red to dark purple is observed in appearance under the action of an applied voltage; the trifluoromethyl or trifluoromethoxy substitution on the phenyl unit not only deepens the HOMO energy level of the monomer and its polymer, but also increases the optical band gap. When used for electrochromic materials, it has the characteristics of low bandwidth, rich colors, fast response time, high coloring efficiency, etc., and can be widely used in electrochromic devices or products and equipment.

[0105] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not intended to limit the embodiments of the present invention. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the embodiments here. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the claims of the present invention.

Claims

1. A conjugated polymer, characterized in that Its structural formula is shown in formula (I) or formula (II): In formula (1) and formula (2), n is independently 3 to 100.

2. The method for preparing a conjugated polymer according to claim 1, wherein The conjugated polymer is prepared from an active precursor by an electrochemical polymerization method; the structural formula of the active precursor is shown in formula (1) or formula (2):

3. The preparation method according to claim 2, characterized in that: The preparation method of the active precursor comprises: under the protection of an inert gas, subjecting an acceptor compound and a stannic compound of EDOT to a Stille or Suzuki cross-coupling reaction in a catalyst and a solvent, thereby obtaining the active precursor; The receptor compounds are: 2,5-dibromotrifluoromethylbenzene and 3,5-dibromotrifluoromethylbenzene.

4. The preparation method according to claim 3, characterized in that: The inert gas includes argon or nitrogen; And / or, the tin hydrocarbon compound of EDOT is 5-tributyltin-3,4-vinyldioxythiophene; And / or, the catalyst comprises at least one of tetrakistriphenylphosphine palladium or bistriphenylphosphine palladium dichloride; And / or, the solvent includes at least one of toluene and N,N-dimethylformamide.

5. The preparation method according to claim 3, characterized in that: The molar ratio of the acceptor compound, the EDOT tin hydrocarbon compound and the catalyst is 1:2-3:0.03-0.1; and / or, the temperature of the Stille or Suzuki cross-coupling reaction is 100° C. to 120° C.; And / or, the Stille or Suzuki cross-coupling reaction time is 24h to 48h.

6. The preparation method according to claim 2, characterized in that: The electrochemical polymerization method comprises using a solution containing the active precursor as an electrolyte solution, and performing electrodeposition in a three-electrode system consisting of a reference electrode, a counter electrode and a working electrode to obtain a thin film material of the conjugated polymer; the working electrode comprises a glassy carbon electrode or ITO conductive glass, the counter electrode comprises a platinum electrode, and the reference electrode comprises an Ag / AgCl electrode.

7. The preparation method according to claim 6, characterized in that: The electrolyte solution further comprises a solvent; the solvent comprises at least one of dichloromethane, chloroform or acetonitrile; And / or, the electrolyte solution further contains a supporting electrolyte; the supporting electrolyte comprises at least one of tetrabutylammonium hexafluorophosphate, tetrabutylammonium tetrafluoroborate or lithium perchlorate; And / or, the concentration of the active precursor in the electrolyte solution is 0.001 to 0.01 mol·L -1 ; and or, the concentration of the supporting electrolyte in the electrolyte solution is 0.05 to 0.15 mol·L -1 .

8. The preparation method according to claim 6, characterized in that: The electrochemical polymerization method adopts constant potential method, constant current method or cyclic voltammetry method to carry out electrodeposition; When the deposition is carried out by constant potential method, the potential of the electrodeposition is 0.9V to 1.2V; And / or, the electrodeposition time is 80s to 200s.

9. An electrochromic material, characterized in that: The invention comprises the conjugated polymer according to claim 1 or the conjugated polymer prepared by the preparation method according to any one of claims 2 to 8.

10. Use of the conjugated polymer according to claim 1 or the conjugated polymer prepared by the preparation method according to any one of claims 2 to 8 in an electrochromic device.

Citation Information

Patent Citations

  • Conjugated polymer as well as preparation method and application thereof

    CN118755059A